Revision of Thisiomorphus Pic (Coleoptera: Mycteridae: Eurypinae) with descriptions of eleven new species from Central and South America and a key to genera of Neotropical Eurypinae - Pollock, Darren A. (Zootaxa, 2016)
The Neotropical eurypine genus Thisiomorphus is revised, based on external structural features of adults. Twelve species are recognized, including the following eleven new species (type areas in parentheses): T. festivus (Panama, Colón Prov.), T. osaensis (Costa Rica, Puntarenas Prov.), T. davidsoni (Brazil, Chapada), T. inaequalis (Ecuador, Napo Prov.), T. caeruleus (Panama, Panamá Prov.), T. brasiliensis (Brazil, Amazonas), T. solisi (Costa Rica, Guanacaste Prov.), T. andrewsi (Panama, Chiriquí Prov.), T. bolivianus (Bolivia, Santa Cruz Dept.), T. curticornis (Ecuador, Sucumbíos Prov.), and T. convergens (Brazil, Pará). A key to the 13 described eurypine genera of Central and South American is provided, along with a key to species of Thisiomorphus. The keys are supplemented with images of habitus and selected structural features, and maps of known distributions are provided.